Faktor-Faktor yang Mempengaruhi Terjadinya Pernikahan Dini pada Remaja di Desa Pelimbangan, Kecamatan Cengal, Kabupaten Ogan Komering Ilir Tahun 2025 - Abel Sutriani; Bina Aquari; Erma Puspita Sari (Jurnal Kesehatan Amanah, 2025)
Early marriage in Indonesia, including in Desa Pelimbangan, Kecamatan Cengal, Kabupaten Ogan Komering Ilir, remains a significant reproductive health issue. This phenomenon leads to negative impacts such as the disruption of education, reproductive health problems, high divorce rates, and intergenerational poverty. This study aims to identify the factors influencing early marriage among adolescents in Desa Pelimbangan in 2025. The factors examined include knowledge, socio-cultural factors, and parental involvement in prevention. This study uses a quantitative approach with a cross-sectional design, involving 95 couples who married between 2022–2024. Data collection was done using a questionnaire that was tested for validity and reliability. The results show that low knowledge is significantly associated with early marriage (p = 0.026; OR = 3.275), with adolescents having low knowledge being 3.275 times more likely to marry early. Socio-cultural factors were not significantly related (p = 0.053; OR = 2.865), while parental involvement was significantly associated (p = 0.018; OR = 3.358). The conclusion of this study suggests enhancing reproductive health education and strengthening parental roles as effective and sustainable strategies to prevent early marriage.